Strategi Pemilihan Bahan Baku Daur Ulang untuk Meningkatkan Profitabilitas di Industri Pengolahan Limbah Plastik - Ulfia, Ulfia; Rahmi, Rahmi; Yusuf, Zulfan; Radhiana, Radhiana; Mukhdasir, Mukhdasir; Humaira, Ajrina (Jurnal Serambi Engineering, 2025)
The plastic waste recycling industry plays a crucial role in reducing environmental impacts while creating economic value through recycling. This study aims to identify strategies for selecting recycled raw materials that can enhance the profitability of the plastic recycling industry. Using a literature review approach, the study explores various sources of raw materials, such as household, industrial, and commercial waste and analyzes their quality, contamination levels, and processing costs. The findings indicate that high-quality raw materials with low contamination levels, such as industrial waste, result in higher production efficiency and lower costs compared to other materials. Additionally, the adoption of modern technologies such as chemical recycling can increase production efficiency by up to 85%. This study contributes by providing a strategic framework for selecting appropriate raw materials, supporting both environmental sustainability and industry profitability.